Nanotherapeutic delivery of antibiotic cocktail enhances intra-macrophage killing of Mycobacterium marinum - Binnebose, Andrea M.; Mullis, Adam S.; Haughney, Shannon L.; Narasimhan, Balaji; Bellaire, Bryan H. (Frontiers in Antibiotics, 2023)
Mycobacterium marinum is a waterborne pathogen responsible for tuberculosislike infections in cold-blooded animals and is an opportunistic pathogen in humans. M. marinum is the closest genetic relative of the M. tuberculosis complex and is a reliable surrogate for drug susceptibility testing. We synthesized and evaluated two nanoparticle (NP) formulations for compatibility with rifampicin, isoniazid, pyrazinamide, and ethambutol (PIRE), the front-line antimycobacterial drugs used in combination against active tuberculosis infections. Improved in vitro antimicrobial activity was observed with encapsulated rifampicin alone or in cocktail combinations of drugs formulated through co-encapsulation in amphiphilic polyanhydride NPs. Broth antimicrobial testing revealed that encapsulation of PIRE in NP resulted in significant increase in antimicrobial activity ranging from >10 to > 3000 fold benefit over soluble at biologically relevant concentrations. M . marinum infected human macrophages treated with NP-PIRE were cleared of viable bacteria in 48 hours following a single treatment representing a > 4 log reduction in CFU with a > 2000 fold increase in antimicrobial activity. The amphiphilic polyanhydride nanoparticles demonstrated the ability to coencapsulate PIRE antibiotics and enhance their antimicrobial activity against M. marinum in culture and in vitro infected macrophages. These data suggest that polyanhydride nanoparticles are a promising nanotherapeutic against Mycobacterium infections through increased intracellular targetting of encapsulated antibiotics.